2007
DOI: 10.1021/jo062452l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of R2PNP(iBuNCH2CH2)3N:  A New Bulky Electron-Rich Phosphine for Efficient Pd-Assisted Suzuki−Miyaura Cross-Coupling Reactions

Abstract: Pro-azaphosphatrane 1a [P(iBuNCH2CH2)3N] reacts with iodine under mild conditions to give [IP(iBuNCH2CH2)3N]I in excellent yield, which on subsequent reaction with ammonia followed by deprotonation with KOtBu provided HN=P(iBuNCH2CH2)3N (3a) in quantitative yield. Reaction of 3a with R'2PCl afforded sterically bulky electron-rich phosphines of the type R'2PN=P(iBuNCH2CH2)3N (4) [R'=Ph (4a), iPr (4b), tBu (4c)]. The Pd(OAc)2/4c catalyst system was particularly efficient for the coupling of arylboronic acids wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 39 publications
3
31
0
Order By: Relevance
“…From Table 3, it can be seen that as expected, the effect of the substituent on the para-position of the arylhalides is mainly depending on the electronegativity of the substituent, electronwithdrawing substituents leading to relatively high yields in the cross-coupling reaction (Table 3, entries 4, 5, 6, 8, 9, 10), while electron-donating substituents resulting in relatively low yields (Table 3, entries 12,13,16,17). While effect of the substituent on the ortho-position of the arylbromide is mainly depending on the size of the substituent, bulky ortho-substituted arylbromide afforded biaryls in relatively low yields, and the yields decreased according to the size increment of the substituent (Table 3, entries 7, 15,19).…”
Section: Resultssupporting
confidence: 58%
“…From Table 3, it can be seen that as expected, the effect of the substituent on the para-position of the arylhalides is mainly depending on the electronegativity of the substituent, electronwithdrawing substituents leading to relatively high yields in the cross-coupling reaction (Table 3, entries 4, 5, 6, 8, 9, 10), while electron-donating substituents resulting in relatively low yields (Table 3, entries 12,13,16,17). While effect of the substituent on the ortho-position of the arylbromide is mainly depending on the size of the substituent, bulky ortho-substituted arylbromide afforded biaryls in relatively low yields, and the yields decreased according to the size increment of the substituent (Table 3, entries 7, 15,19).…”
Section: Resultssupporting
confidence: 58%
“…Previous work from our group has established that the commercially available proazaphosphatrane 8 [11] bearing isobutyl groups on the PN 3 nitrogens and its derivative (t-Bu) 2 P À N=P(i-BuNCH 2 CH 2 ) 3 N) 9a [12] Scheme 1. Pd-catalyzed double N-arlyation of primary amines with 2,2'-dihalobiphenyls.…”
mentioning
confidence: 99%
“…(Scheme 1, both first synthesized in our laboratories) are highly effective ligands for several palladium-catalyzed cross-coupling reactions of aryl bromides, iodides and chlorides, such as Suzuki [12,13] , Stille [14] , a-arylation [15] and Buchwald-Hartwig amination reactions. [16] We have suggested that the unusually high activity of 8 and 9a as supporting ligands in Pd-catalyzed coupling reactions is due primarily to their steric bulk and the uniquely electron-rich nature of their trivalent phosphorus atoms stemming from the geometrically favorable arrangement of the three sp 2 nitrogens contributing their unhybridized p electron lone pair density to the phosphorus and the possibly temporary N!P transannulation donating the bridgehead nitrogens lone pair to the phosphorus in the proazaphosphatrane framework in each of these molecules.…”
mentioning
confidence: 99%
See 2 more Smart Citations